Inovation Heat Treatment of Coining Dies - Analysis of the Microstructural Parameters Tool Steels - Kalincová, Daniela; Ťavodová, Miroslava; Kaštan, Rudolf (Manufacturing Technology Journal, 2016)
This paper deals with research of the heat treatment of tool steels Böhler K 455, K605 that are determined for production of tools for minting circulation coins. The aim of the research was to determine the impact of introduction of innovative heat treatment on the structural parameters and lifetime of coining dies. Experimental part presents the results of purity evaluation at semi-products with use of EDX analyse of the non-metallic inclusions, also microstructure evaluation, measurement of the size austenite grain after application of innovative heat treatment also. After ending of analysis and evaluation of lifetime coining dies, new parameters of heat treatment for using at the production were proposed.
Keywords: tool steel; innovation; thermal treatment; microstructure; size of austenitic grain; lifetime; coining dies